The energy-pollution-health nexus: A panel data analysis of low- and middle-income Asian nations - Farhad Taghizadeh-Hesary; Ehsan Rasoulinezhad; Naoyuki Yoshino; Chang Youngho; Farzad Taghizadeh-Hesary; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2020)
An energy resource as a production input plays a major role in various economic sectors, including commodity production, transportation, and electricity generation. However, increased energy consumption may lead to more air pollution, resulting in negative health impacts in a society. The main purpose of this study is to investigate the relationship between energy consumption and health issues (e.g., tracheal, bronchial and lung cancer, respiratory diseases, prevalence of undernourishment, death ratio due to exposure to both outdoor and household air pollution) using generalized method of moments estimation technique for data from 18 Asian countries (both low- and middle-income) over the period 1991−2018. It is found that carbon dioxide (CO2) emissions per capita in low- and middle-income Asian nations result in the positive prevalence of lung and respiratory diseases. With regard to fossil fuel consumption, the findings demonstrate that this variable increases the risk of lung and respiratory diseases. In addition, the results demonstrate the significant effect of CO2 emissions and fossil fuel consumption on undernourishment and death ratio. Furthermore, we find that gross domestic product per capita and health care expenditure may help reduce undernourishment and death ratio. The conclusion recommends conducting rapid energy transition programs, improving energy efficiency, and reducing energy intensity in low- and middle-income Asian countries, in order to strengthen their national health security.
Keywords: I15; Q41; C33; 330; energy consumption; health issues; low- and middle-income Asian countries; panel data estimation